ANALISIS POLITIK HUKUM PEMBENTUKKAN INSTRUKSI PRESIDEN (INPRES) NOMOR 1 TAHUN 2022 TENTANG OPTIMALISASI PELAKSANAAN PROGRAM JAMINAN KESEHATAN NASIONAL (JKN) - Yati, Lisa Medika (TAHKIM, 2025)
Health is a human right and must therefore be realized in accordance with the ideals of the Indonesian nation as enshrined in the Pancasila and the 1945 Constitution of the Republic of Indonesia. In early 2022, President Joko Widodo issued Presidential Instruction (Inpres) Number 1 of 2022 concerning the Optimization of the Implementation of the National Health Insurance (JKN) Program. This is intended to encourage Indonesians to register for the JKN program through the BPJS Kesehatan (Social Security Agency). Based on the Presidential Instruction issued by President Jokowi, JKN will collaborate with 30 Indonesian Ministries. This includes requirements for obtaining driver's licenses (SIM), vehicle registration certificates (STNK), police clearance certificates (SKCK), membership for prospective Hajj and Umrah pilgrims, and requirements for obtaining BPJS Mandatory People's Business Credit (KUR). The implementation of Presidential Instruction (Inpres) Number 01 of 2022 concerning the Optimization of JKN requires JKN program participation as an attached requirement for public service processes. This policy tends to force people to join BPJS Kesehatan. Many parties are pro and con regarding Presidential Instruction Number 1 of 2022. This prompted the author to analyze this matter, with the formulation of the problem: Does the formation of Presidential Instruction Number 1 of 2011 concerning the Optimization of the Implementation of the National Health Insurance Program comply with the regulatory formation process? What is the legal policy of the formation of Presidential Instruction Number 1 of 2011 concerning the Optimization of the Implementation of the National Health Insurance Program? The purpose of this research is to examine the legal policy of the formation of Presidential Instruction Number 1 of 2021 concerning the Optimization of the Implementation of the National Health Insurance Program. The type of research conducted is normative research (literature). Normative law is intended to examine and examine the legal norms of Presidential Instruction Number 1 of 2011 concerning the Optimization of the Implementation of the National Health Insurance Program. The results of this research, first, the formation of Presidential Instruction Number 1 of 2022 does not comply with the proper legal regulation-making procedures and harms the public service system. Second, the legal policy of the formation of Presidential Instruction Number 1 of 2022 is legally repressive. Keywords: health, JKN, BPJS, Presidential Instruction, services